2010
DOI: 10.1590/s1678-86212010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Álcalis incorporados ao aluminato tricálcico: efeitos na hidratação

Abstract: Resumoaluminato tricálcico (C 3 A) é a fase que reage mais rápido na hidratação do cimento quando em contato com a água. Geralmente, a forma cristalina sintetizada durante o processo de clinquerização é cúbica. No entanto, o íon Na + pode ser incorporado na estrutura cristalina do C 3 A, em substituição ao Ca 2+ , levando à modificação da forma cristalina cúbica, para a ortorrômbica (Na-C 3 A). Embora alguns estudos tenham investigado a interferência desta fase modificada na hidratação do cimento, algumas lacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Studies where grinded original copper slag was incorporated in mortar and concrete as partial substitute of cement in small proportions, less than 20%, show that compressive strength and other characteristics such as porosity and durability were increased, when compared to reference mixtures [1][2][3][4][5], although some studies [6] does not revealed increments in strength. When grinded copper slag is used in cement mixtures as partial cement substitute, after its use as abrasive, the compressive strength decrease when compared to the reference mixtures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies where grinded original copper slag was incorporated in mortar and concrete as partial substitute of cement in small proportions, less than 20%, show that compressive strength and other characteristics such as porosity and durability were increased, when compared to reference mixtures [1][2][3][4][5], although some studies [6] does not revealed increments in strength. When grinded copper slag is used in cement mixtures as partial cement substitute, after its use as abrasive, the compressive strength decrease when compared to the reference mixtures [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent this, gypsum (CaSO.2H 2 O) is added to the clinker manufacturing process of Portland cement. According to Kirchheim et al (2010) [8], an example of the action of the C 3 A can be seen in the execution of Iberê Camargo museum in Porto Alegre, where it was used white Portland cement with C 3 A contents above 9%. The calcium silicates (C 3 S e βC 2 S) are responsible for about 75% of the constitution of ordinary Portland cement, exerting a dominating role in determining the characteristics of hardness, also known as the rate of development of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Cements with high hydration heat, hydrate faster compared to cements that generate less heat of hydration (Taylor, 1967) [9]. Kirchheim et al (2010) [8] add that in certain works use large amounts of concrete, its thermal conductivity can be low and with a high heat release due to the hydration reaction, which can generate cracks through thermal retraction. According to Mehta and Monteiro (2008) [4] the heat of hydration can sometimes be unfavorable, for example, in the mass-concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the higher alkali content, orthorhombic C3A has a very complex crystal structure, characterized by large structural voids, making it more soluble and reactive than cubic C3A. Therefore, orthorhombic C3A content must be limited in cements for special applications, such as in sulfate-resistant cements [35].…”
Section: Reactivity Of Clinker Phasesmentioning
confidence: 99%
“…Influence of spraying on hydration __________________________________________________________________________________________________________________________________________________________________________________________________________________________________ __________________________________________________________________________________________________________________________________________________________________________________________________________________________________ Renan Pícolo Salvador 133 the increase in temperature [35], the spraying process may lead to the formation of AFm phases at the moment of accelerator addition. Larger amounts of gypsum in cement may be required to suppress the formation of AFm phases due to the increase in temperature caused by spraying.…”
Section: Evolution Of Temperaturementioning
confidence: 99%